Twin block appliance: Effect on pharyngeal airway - Thapa, Vivek Bikram; Shrestha, Amrita; Sherchan, Prabesh; Poudel, Prakash; Joshi, Luna (Journal of Kathmandu Medical College, 2018)
Background: Mandibular retrusion is the main cause of Skeletal Class II malocclusion characterized by skeletal retrusion of mandible with skeletal or dentoalveolar protrusion of maxillary. Objectives: This study was conducted to evaluate effect of treatment with twin-block appliances on pharyngeal dimensions. Methodology: This study was conducted in in the Department of Orthodontics & Dentofacial Orthopedics in Kathmandu Medical College. Twenty patients of age group 7 to 14 years with skeletal class II malocclusion with mandibular retrusion were selected. Variables evaluated were depth of nasopharynx; height of nasopharynx; depth of oropharynx; depth of hypopharynx; soft palate length; soft palate thickness and soft palate inclination. The lateral cephalograms were obtained for all subjects before the start of treatment and after a follow-up period of approximately three months in treatment. Results: Results showed that depth of nasopharynx increased by 1 mm, height of nasopharynx increased by 0.78 mm, depth of nasopharynx increased by 1.97 mm, depth of hypopharynx increased by 0.79 mm, soft palate length decreased by 4 mm, soft palate thickness increased by 2 mm and soft palate inclination decreased by 7.01 mm. The results for depth of pharynx and soft palate thickness were statistically significant. Conclusion: This study concluded that the use of twin block appliance for class II patients corrects sagittal dimension of oropharynx and hypopharynx. Early intervention for mandibular retrognathism in class II malocclusion helps enlarge the airway dimensions and decrease potential risk of obstructive sleep apnea syndrome for growing patients in the future.